Radiocarbon dating of agrarian terraces by means of buried soils - Puy, Arnald; Balbo, Andrea Luca; Bubenzer, Olaf (Radiocarbon, 2016)
Abstract: Soils buried under terrace fills have been widely used to date the construction of ancient agrarian terraces. The reliability of the obtained radiocarbon dates entirely depends on the degree of preservation and isolation of the Ab horizons and on the amount of embedded older carbon. To assess these caveats, we analyzed 14 14C dates (11 on charred material and 3 on the bulk organic fraction) obtained from buried soils under Andalusi terrace fills in Ricote, Spain (AD 711-1492). The preservation of Ab horizons was assessed through bulk analyses [particle size distribution (PSD), carbon analyses, magnetic susceptibility (Mag Sus)] and statistics [Welch’s ANOVA, MANOVA (Wilk’s lambda) and effect size tests]. The effects of older carbon were quantified through the systematic dating of Ab horizons within the earliest terrace cluster of Ricote. Our results show that (1) Ab horizons were not disturbed nor mixed with the terrace fills above; (2) the dates determined from the bulk organic fraction were statistically significantly older than those provided by the charred material, probably due to the higher stability of the microcharcoal fraction; and (3) the earliest dates measured on charcoal clustered reliably around cal AD 989-1210, suggesting that the first Andalusi irrigated terraces of Ricote were built between the end of the 10th and the beginning of the 13th centuries AD.
Gesehen am 17.03.2017